MARKETING IN HOTEL CORPORATION AND SPORT MANAGEMENT - Miodrag Koprivica; Vasilj Koprivica; Slobodan Živkucin (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Sportsmen are customers of hotel services, therofore sports managers must have about their organization and work. In the hotel business there are at least three involved parties, and each one of them has one or more main goals. Main goal of the hotel owners is to make profit, hotel employees is to earn their salaries and the hotel guests main goal is to get the satisfac- tion through the services that hotel offers. Main assignment of the hotel management is to create business strategy which would lead to satisfaction of all three involved parties. Favoring one of the involved party's needs that leads to other parties disadvanta- ge is not a formula of successful management. Mission and vision of the hotel business are determined by the hotel owners them- selves. The goal of the hotel management is to "translate" the general business philo- sophy into goals, plans and measures in order to achieve the before mentioned philo- sophy. Determining of the (really) achievable vision, "dream of success" if you will, is the foundation of the total and successful business politics in the hotelier business. The goal of this work is to answer the questions of the usefulness of the hotels marketing mix, diverse commercial tools and the resource size which hotels use for mar- keting. All in the function of general alignment of the universal business politics and concrete plans and functions.